Local homogeneity in fuzzy topological spaces - Samer Al Ghour (International Journal of Mathematics and Mathematical Sciences)
Three types of local homogeneity in L-topological spaces are introduced and studied, and each is characterized and proved to be a good extension of local homogeneity in ordinary topological spaces. Many implications concerning them are introduced. The study deals with the L-topologically generated topological spaces.